2010
DOI: 10.5507/bp.2010.050
|View full text |Cite
|
Sign up to set email alerts
|

Management of Two Cases of Desquamative Gingivitis With Clobetasol and Calendula Officinalis Gel

Abstract: Background. The purpose of this paper is to describe two cases of desquamative gingivitis (DG) that were treated with a topic gel containing clobetasol propionate and Calendula officinalis L in an acetate tray over two years.Methods. Two patients with a diagnosis of lichen planus presenting as DG who had undergone previous treatments for this condition with no significant results, were treated by a handling gel containing clobetasol, nystatin, Calendula oficcinalis L and pectin in custom trays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…3 They contain flavonoids, coumarins, essential oils and fatty acids. 4 It has been reported that Calendula promotes wound healing and might be effective in shortening the duration of wound healing. 4 Calendula extract has been used in Europe since before the 12th century primarily as a topical antiinflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…3 They contain flavonoids, coumarins, essential oils and fatty acids. 4 It has been reported that Calendula promotes wound healing and might be effective in shortening the duration of wound healing. 4 Calendula extract has been used in Europe since before the 12th century primarily as a topical antiinflammatory agent.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal, homeopathic, and Chinese traditional therapies Several homeopathic/herbal medicines including Aloe barbadensis miller (aloe vera) (Choonhakarn et al , 2008; Salazar‐Sánchez et al , 2010), Calendula officinalis (Machado et al , 2010), curcuminoids (Chainani‐Wu et al , 2007), Ignatia amara (Mousavi et al , 2009), Portulaca oleracea (purslane) (Agha‐Hosseini et al , 2010), and hinokitiol (Nagao and Sata, 2011) have been investigated for OPL treatment. Only curcuminoids (CU) and aloe vera (AV) (in more than one RCT) have been studied in RCTs (Table 7).…”
mentioning
confidence: 99%
“…C.officinalis contains triterpenoid fatty acid esters, with the most abundant are the lauryl, myristoyl, and palmitoyl esters of faradiol which have antiinflammatory effects (38).…”
Section: Officinalis In Treatment Of Oral Lichen Planusmentioning
confidence: 99%